Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

La charge mentale, une double peine pour les femmes - Flèche, Sarah; Sénécal, Laura (CNRS Le journal, 2021)
Une étude menée par des économistes analyse comment la charge mentale que les femmes subissent encore majoritairement aujourd’hui ne leur permet pas de concilier équitablement vie professionnelle et familiale et nuit à leur bien-être. Un billet à lire sur le blog de la revue Dialogues économiques.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; charge mentale; discipline; inégalités; inégalités hommes-femmes; projet charge mentale; périodes historiques; ressource en ligne; sciences de la gestion; systèmes d'oppressions; thématiques; travail; travail domestique; économie

Postcolonial / Décolonial: la preuve par l'art - Toussaint, Evelyne (Presses universitaires du Midi, 2021)
Les liens entre art contemporain, histoire coloniale, postcolonialisme et mouvements décoloniaux sont anciens et multiples. Des artistes, en Occident et ailleurs, depuis plusieurs décennies déjà, revisitent opportunément des concepts que les études postcoloniales ont approfondis ou inventés - agency (agentivité), mimicry (mimétisme/simulacre) ou essentialisme stratégique -, en autant d'outils utiles à démêler la complexité des relations coloniales et, au-delà, de toutes les relations de domination. Des auteurs, relevant de ces champs d'études conservant aujourd'hui toute leur actualité politique, théorique et polémique, disent en retour tout l'intérêt qu'ils portent à la création contemporaine. Associant vingt historiens de l'art et chercheurs en littérature, philosophie, droit ou psychanalyse, Postcolonial/Décolonial. La preuve par l'art réunit des textes portant sur des productions artistiques (Betye Saar, Fred Wilson, Sarkis, Lidwien van de Ven, Voluspa Jarpa, Iris Kensmil, Jean Renoir et bien d'autres), des propositions institutionnelles (Centro de Arte y Comunicación de Buenos Aires, Biennale de Venise ou Van Abbemuseum d'Eindhoven), l'historiographie de l'histoire de l'art ou celle du droit. Une place particulière est réservée aux singularités artistiques, théoriques et juridiques en Amérique latine, lieu d'émergence des théories décoloniales–Page 4 de la couverture.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; droit; féminisme décolonial; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; science politique et droit; sciences de la gestion; thématiques; économie

Feminist economics: Theoretical and political dimensions feminist economics - Agenjo-Calderón, Astrid; Gálvez-Muñoz, Lina (American Journal of Economics and Sociology, 2019)
Feminist economics is a school of economic thought and political action that gained important visibility during the 1990s, although its origins can be dated back to the mid-19th century. Since then, feminist economics has developed its own concepts, analytical frameworks, and methodologies. With gender as a central category, it seeks a more integral and humane comprehension of the economy and of the processes of inclusion and exclusion taking place in it. In addition, feminist economics has grown into a political practice that aims at improving the functioning of the economic system so that all people can have access to a dignified life on the basis of equality. This article presents a general systematization of these theoretical and political dimensions, particularly focusing on the critique of the neoclassical paradigm and its political correlates. We connect the epistemological, methodological, and conceptual contributions of feminist economics, as well as its propositions for transformative action, to specific debates on economic issues, such as the ecological emergency, crisis and austerity, the commodification of life, and the liberalization of trade.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; genre; identités LGBTQIA2+; politique; périodes historiques; ressource en ligne; sciences de la gestion; sciences humaines; sociologie; thématiques; économie; égalité des sexes

Big data for (not so) small loans: Technological infrastructures and the massification of fringe finance - Langevin, Marie (Review of International Political Economy, 2019)
This article examines the evolution of the sociotechnical systems that is leading to a massive increase in the overall indebtedness of marginalized populations in the Global South. I analyze the processes through which Big Data (or alternative data) technologies are transforming the infrastructure of fringe finance, the nature of its power relations, and its capacities. The article identifies the consequences of these technological transformations on financial practices and illustrates the qualitative nature of the changes involved. I propose that while these innovations have increased the power of this market to capture value, they have also increased risks to indebted populations and the infrastructure's stability. I argue that these financial practices, enhanced by the power of Big Data, have made the infrastructure of fringe finance dangerously hermetic to careful consideration of the productive capacities of those being targeted for inclusion into the formal financial system, thereby making it potentially dysfunctional.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; inclusion financière; périodes historiques; ressource en ligne; sciences de la gestion; économie

Les femmes, l’entreprise et le droit 2019: une décennie de réformes - World Bank Group (World Bank, 2019)
The World Bank Group’s Women, Business and the Law examines laws and regulations affecting women’s prospects as entrepreneurs and employees across 187 economies. Its goal is to inform policy discussions on how to remove legal restrictions on women and promote research on how to improve women’s economic inclusion. Women, Business and the Law 2019: A Decade of Reform introduces a new index measuring legal rights for women throughout their working lives in 187 economies. The index is composed of 35 data points grouped into eight indicators. The data covers a 10-year period not only to understand the current situation but to see how laws affecting women’s equality of opportunity have evolved over time. The index assesses economic rights at milestones spanning the arc of a woman’s working life: the ability to move freely; starting a job; getting paid; legal capacity within marriage; having children; running a business; managing assets; and getting a pension.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; droits des femmes*; entrepreneuriat; femmes*; périodes historiques; sciences de la gestion; thématiques; économie; égalité des sexes

The global gender gap report 2016 (World Economic Forum, 2016)
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; approches et analyses; discipline; inégalités; périodes historiques; ressource en ligne; sciences de la gestion; systèmes d'oppressions; économie; égalité des sexes

1. Genre et théorie économique - Talahite, Fatiha (Regards croisés sur l'économie, 2014)
L’économie est l’une des dernières sciences humaines et sociales à avoir intégré le genre. Cet article interroge la résistance de la science économique au genre et montre comment celui‑ci fut finalement introduit, à travers trois moments clés de cette histoire : le débat sur la valeur du travail domestique ; la critique féministe en épistémologie et histoire de la pensée économique ; la construction d’une économie néoclassique du genre à partir des travaux de Gary Becker. Grâce à l’importante production qui en a résulté, l’économie a certes pu rattraper son retard, mais elle a absorbé le genre sans avoir été ébranlée dans ses fondements. L’économie du genre s’est moulée dans les divisions de la science économique.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; discipline; histoire et politique; projet charge mentale; périodes historiques; sciences de la gestion; sciences humaines; thématiques; travail; travail domestique; économie; épistémologie

Les femmes et le marché du travail au Québec : portrait statistique - Ruth, Rose (Service aux collectivités de l'UQAM/Comité consultatif Femmes en développement de la main-d'oeuvre/Conseil d'intervention pour l'accès des femmes au travail, 2013)
« L'objectif de cette étude, effectuée par l’économiste Ruth Rose, professeure associée à l’Université du Québec à Montréal, est de présenter un portrait statistique de la situation des femmes québécoises sur le marché du travail, de son évolution au cours des années récentes et de la comparer à celle des hommes, en tenant compte de la diversité de la population féminine. » (2013, 1)
Mise à jour de l'étude publiée en 2005 et intitulée Les femmes et le marché de l'emploi, la situation économique et professionnelle des Québecoises, réalisée par le Comité consultatif Femmes en développement de la main-d'oeuvre. https://biblio.cdeacf.ca/cgi-bin/koha/opac-detail.pl?biblionumber=222101&query_desc=Les%20femmes%20et%20le%20marché%20du%20travail%20au%20Québec%20%3A%20portrait%20statistique
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; amériques; approches et analyses; discipline; périodes historiques; québec; rapports sociaux de sexe; recherche partenariale; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; travail; économie

Working women, caring men, and the family bank: Ideal gender relations after the Washington Consensus dans Developing partnerships: gender, sexuality, and the reformed World Bank - Bedford, Kate (Developing partnerships: gender, sexuality, and the reformed World Bank, 2009)
A critique of how the World Bank encourages gender norms, Developing Partnerships argues that financial institutions are key players in the global enforcement of gender and family expectations. By combining analysis of documents produced and sponsored by the World Bank with interviews of World Bank staffers and case studies, Kate Bedford presents a detailed examination of gender and sexuality in the policies of the world’s most influential development institution.
Section: xxxiv, 292 pages : illustrations
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; féminisme décolonial; histoire et politique; inégalités; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sciences de la gestion; sud global; systèmes d'oppressions; thématiques; économie

Visées sociales et visées économiques : impact de la cohabitation sur la dynamique de développement d'une entreprise d'économie sociale issue d'un organisme communautaire de services - Guay, Danielle (Université du Québec à Montréal, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; IREF; discipline; mémoires/thèses; organisme communautaire; périodes historiques; sciences de la gestion; sciences humaines; sociologie; économie; économie sociale

L'économie sociale du point de vue des femmes - Corbeil, Christine; Descarries, Francine; Galerand, Elsa (LAREPPS, 2002)
Actes du colloque
https://www.socioeco.org/bdf_fiche-document-5338_fr.html
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; discipline; division sexuelle du travail; périodes historiques; québec; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; travail; économie; économie sociale